Association Between Allergen Sensitization and Anaphylaxis in Patients Visiting a Pediatric Emergency Department - Lee, Won Seok; Cha, Lily Myung-Jin; Han, Man Yong; Lee, Kyung Suk (Frontiers in Pediatrics, 2021)
Anaphylaxis, a severe allergic disease, can be triggered by various causes. This study investigated the association between allergic sensitization and anaphylactic symptoms and the severity of anaphylaxis in children. A retrospective review of 107 pediatric patients with anaphylaxis was performed between January 1, 2015, and December 31, 2017; 74 patients underwent allergen testing for specific immunoglobulin E. Allergic sensitizations and associations with anaphylactic symptoms and severity were investigated. Overall, 64 (86.5%) patients were sensitized to food or inhalant allergens. In children under two years of age, 90.5% were sensitized to food (P=0.001); in those over six years of age, 84.6% were sensitized to inhalant allergens (P=0.001). Milk sensitization was significantly associated with severe anaphylaxis (P=0.036). The following symptoms showed significant associations with certain allergen sensitizations: facial edema with food; wheezing with milk; dyspnea with mite, etc. Certain allergen sensitizations presenting as risk factors for anaphylactic symptoms: wheat (adjusted odds ratio [aOR] =4.644, P=0.044) and nuts (aOR=3.614, P=0.041) for wheezing, nuts (aOR=5.201, P=0.026) for dyspnea, and milk (aOR=4.712, P=0.048) for vomiting. The allergen sensitization status differed according to the age of the children experiencing anaphylaxis. The severity, symptoms, and signs of anaphylaxis differed depending on the allergen sensitization status.